Ketogenic Diet and microRNAs Linked to Antioxidant Biochemical Homeostasis - Roberto Cannataro; Maria Cristina Caroleo; Alessia Fazio; Chiara La Torre; Pierluigi Plastina; Luca Gallelli; Graziantonio Lauria; Erika Cione (MDPI AG, 2019)
Recently, we demonstrated the capability of the ketogenic diet (KD) to influence the microRNA (miR) expression profile. Here, we report that KD is able to normalize miR expression in obese subjects when compared with lean subjects. By applying two different bioinformatics tools, we found that, amongst the miRs returning to comparable levels in lean subjects, four of them are linked to antioxidant biochemical pathways specifically, and the others are linked to both antioxidant and anti-inflammatory biochemical pathways. Of particular interest is the upregulation of hsa-miR-30a-5p, which correlates with the decrease of catalase expression protein in red blood cells.